Effects of Enzyme Types and Extraction Conditions on Protein Recovery and Antioxidant Properties of Hydrolysed Proteins Derived from Defatted Lemna minor - Tran, Hai Chi; Thi Le, Hong Anh; Le, Thanh Thanh; Phan, Van Man (Applied Science and Engineering Progress, 2021)
Lemna minor (L. minor), the common duckweed, contains a high protein substance and is considered as a good source of potential bioactive peptides. The objective of this study is to investigate the effect of enzymatic hydrolysis times (60–180 min) and enzyme concentrations (0.5–3.5%v/w) with Alcalase and Flavourzyme on the recovery, hydrolysis degree (DH), and antioxidant properties of peptides derived from defatted L. minor. The protein recovery, hydrolysis degree (DH), and antioxidant activities obtained by enzymatic were compared with the alkaline treatment method. The results showed that the protein recovery, DH values, and antioxidant activities were enhanced by increasing the enzyme concentration and hydrolysis time. Specifically, the recovery of protein and DH values reached the highest level after the enzymatic hydrolysis by Flavourzyme or Alcalase at 1.5 v/w enzyme for 120 min. At the same enzymatic hydrolysis condition, the samples hydrolyzed by Flavourzyme had a higher inhibitory effect on the ABTS•+ and DPPH•+ radical scavenging than those hydrolyzed by Alcalase and the alkaline treatment. Further study also showed that the DH values, amino acid contents, and antioxidant activities of the protein extracts were positively correlated. Thus, the extractions with Flavourzyme and Alcalse were a good method to produce a significant amount of amino acids and smaller peptides.